Realizacja przedmiotu "Wychowanie do życia w rodzinie" w Polsce a standardy edukacji seksualnej w Europie w kontekście zachowań ryzykownych podejmowanych przez młodzież = Realization of the subject "Education for Family Life" in Poland and the standards of sex education in Europe in the context of risk behaviours undertaken by adolescents - Komosińska, Krystyna; Kowalewska, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The topics which are introduced nowadays within the subject "Education for Family Life" are determined by the Regulation of the Minister of National Education of 17th February, 2012 (the Journal of Laws, 2012, No 300). In 2008 WHO Regional Office for Europe, Federal Office for Health Education and WHO Collaborating Centre for Sexual and Reproductive Health in Cologne appointed a group of experts from Europe to develop "Standards of Sex Education in Europe".
Keywords: standards of sex education; Education for Family Life; risk behaviours; youth; standardy edukacji seksualnej; edukacja do życia w rodzinie; zachowania ryzykowne; młodzież